2020
DOI: 10.1101/2020.09.14.296244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy induced accumulation of lipids inpgrl1andpgr5ofChlamydomonas reinhardtiiunder high light

Abstract: Chlamydomonas (C) reinhardtii cells (wild-type CC125 and 137AH, and cyclic electron transport dependant mutants pgrl1 and pgr5) were grown in high light 500 μmol photons m-2 s-1 where the growth was significantly enhanced after three days. The starch and lipid contents were also increased; however, starch content was decreased in pgr5. Further, the Nile Red fluorescence shows that a significant amount of lipid bodies were observed in pgr5 cells under high light. Similarly, the electron micrographs show that la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…All these results suggest that light activation and light stress operate via related, but not necessarily identical, pathways. We propose that, while limiting light might only activate DGAT3 expression and TAG accumulation in the chloroplast ( Figure 6A), high light might also activate the expression of other enzymes that participate either in the chloroplast or the ER, as shown in Figure 6B and as also proposed previously (Chouhan et al, 2020;Goold et al, 2016). In addition, while DGAT3 expression might be a target of the light signal transduction cascade, other enzymes involved in TAG synthesis might be targets of stress/ROS signaling cascades ( Figures 6A and 6B).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…All these results suggest that light activation and light stress operate via related, but not necessarily identical, pathways. We propose that, while limiting light might only activate DGAT3 expression and TAG accumulation in the chloroplast ( Figure 6A), high light might also activate the expression of other enzymes that participate either in the chloroplast or the ER, as shown in Figure 6B and as also proposed previously (Chouhan et al, 2020;Goold et al, 2016). In addition, while DGAT3 expression might be a target of the light signal transduction cascade, other enzymes involved in TAG synthesis might be targets of stress/ROS signaling cascades ( Figures 6A and 6B).…”
Section: Discussionsupporting
confidence: 82%
“…Even though not all enzymes that can synthesize TAGs have been evaluated in our high light experiments, one could hypothesize that a more general response to stress is activated in these conditions compared to moderate light. Recently, it was demonstrated that high light induces ROS, which leads to TAG accumulation, in agreement with an increase in DGAT2A and PDAT (Chouhan et al, 2020). All these results suggest that light activation and light stress operate via related, but not necessarily identical, pathways.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…grown in BBM [49] and in other wastewaters, such as in vinasse (32%) and raw chicken manure (35%) [40]. Palmitic acid was also shown to be the main fatty acid produced under sodium acetate stress [50], at nutrient limitation [48,51,52], at high temperatures [53], and at high light intensity [54]. Indeed, a limitation in the content of nitrogen and phosphorous in the AP-POME culture supernatants is observed after 5 days of cultivation (Table 2).…”
Section: Plos Onementioning
confidence: 99%